SOSIALISASI INVESTASI YANG BERTANGGUNG JAWAB: MENYELAMATKAN SISWA SMA DARI BAHAYA JUDI ONLINE DI SMAN 1 PARUNG PANJANG KABUPATEN BOGOR - Eko Prasetyo (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service is entitled socialization of responsible investment: saving high school students from the dangers of online gambling at SMAN 1 Parung Panjang, Bogor Regency. The general objective of this community service activity is to provide training and practical knowledge of responsible investment to save high school students from the dangers of online gambling. The methods used are survey method and direct material delivery as well as simulation and discussion on successful investment and tragic stories related to online gambling, so that students can understand the implications of their financial decisions. The conclusion of this community service is that assistance will be provided in responsible investment to save high school students from the dangers of online gambling by forming investment groups in order to form the character of students who can make the right investment.